1992
DOI: 10.1021/ma00045a034
|View full text |Cite
|
Sign up to set email alerts
|

Deformation mechanisms and plastic resistance in single-crystal-textured high-density polyethylene

Abstract: Highly textured high-density polyethylene (HDPE) prepared by plane strain compression in a channel die was used as a macroscopic approximation to a single crystalline material to study the plastic deformation mechanisms. Samples cut out of the textured rectangular bars were subjected to tensile, compressive, and simple shear deformation in different crystallographic orientations, specifically chosen to probe the deformation resistances of specific crystallographic mechanisms of deformation. The degree of domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(129 citation statements)
references
References 12 publications
4
125
0
Order By: Relevance
“…The results presented here pose new challenges to the modeling efforts reported in current literature [10][11][12][13][19][20][21][22][23][24][25]. As described earlier, previously reported models predict the formation of the (001) fiber component (with a slight misalignment in some cases); they do not predict the formation of either the near-(011) component or the weaker (010) component.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The results presented here pose new challenges to the modeling efforts reported in current literature [10][11][12][13][19][20][21][22][23][24][25]. As described earlier, previously reported models predict the formation of the (001) fiber component (with a slight misalignment in some cases); they do not predict the formation of either the near-(011) component or the weaker (010) component.…”
Section: Discussionmentioning
confidence: 68%
“…These can produce large unloading strains, especially in tensile loaded samples, and potentially cause significant changes in the underlying texture in the sample. Therefore, the textures reported in previous studies [10][11][12][13][14][15]19,[22][23][24] correspond to "deformed and relaxed" textures in the samples, and may not represent accurately the "deformation only" texture in the sample.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The type of chain slip does not need to be specified either; but given that the easiest chain slip systems in PE are (100) [001] and (010)[001] [10], these are expected to dominate the orientation process.…”
Section: The Proposed New Crystalline Chain Slip Modelmentioning
confidence: 99%
“…In this connection, two deformation mechanisms have been discussed, those are a) an approach based on adiabatic melting and recrystallization [3], and b) the deformation by crystallographic slip [4]. The major part of publications, favor the occurrence of the latter mechanism even for a wide range of strain [5][6][7]. Recently it could be shown that this mechanism is governed by nucleation and propagation of dislocations [8][9][10], although it was also reported [9] that in some polymer systems other deformation modes have to be considered in the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%